2007
DOI: 10.1016/j.amjmed.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Weight Loss Advice on Internet Forums

Abstract: Most advice posted on highly active Internet weight loss forums is not erroneous or harmful. However, clinical and research strategies are needed to address the quality of medication-related advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 16 publications
5
25
1
3
Order By: Relevance
“…This is similar to a study by Hwang et al [6] that illustrated that questions to online health communities are answered with high quality information very frequently. Further, information that was inaccurate or dangerous was very quickly corrected..…”
Section: P#1992supporting
confidence: 83%
“…This is similar to a study by Hwang et al [6] that illustrated that questions to online health communities are answered with high quality information very frequently. Further, information that was inaccurate or dangerous was very quickly corrected..…”
Section: P#1992supporting
confidence: 83%
“…However, while 2D web interventions often provide interaction tools (e.g., message boards, e-mails, and chat rooms) few studies have examined the importance of interaction and support, particularly among participants. Hwang et al [19] found that participants of the online weight loss community "SparkPeople" used the website's discussion forums to receive motivation, encouragement, general weight loss information, and share personal stories. Participants felt interactions were convenient, anonymous, non-judgmental, and reciprocal.…”
Section: Prior Intervention Researchmentioning
confidence: 99%
“…Participants in Internet health communities exchange social support by communicating primarily via discussion forums, as well as blogs and e-mails (Hwang et al, 2007;Sarasohn-Kahn, 2008). The unique process of communicating via online forums appears to shape how participants experience social support (Tanis, 2008;White & Dorman, 2001).…”
Section: Elmer V Bernstammentioning
confidence: 99%